Assessment preferences cooling water to the corrosion or making incrustation in TPP - Bosiljka Stojanović; Jovan Đuković; Miladin Drobnjak (Zaštita Materijala)
The tendency of cooling water to the corrosion or inlay is estimated by the calculated index Langelier Saturation Index, Ryznar Stability Index, Larson-Skold Index and others. This paper gives an overview of the tendency of cooling water in TPP Ugljevik in short intervals during 2015. and 2016.